Getting off to a good start? A multi-site study of orienting student nurses during aged care clinical placements - Robinson, A.; Abbey, J.; Abbey, B.; Toye, Christine; Barnes, L. (Elsevier Ltd., 2009)
Summary Undergraduate nursing students rate residential aged care an unattractivecareer option. Some likely causes are beyond the control of the sector, otherswithin or partly within its control. Addressing the problem – the aim of the modellingconnections project – is important and urgent.This paper, derived from that project, profiles the characteristics of 12 residentialaged care facilities across four Australian states, 66 of their staff and 53 studentnurses undertaking clinical placements. Staff and student responses to a 30-itemorientation experience survey are compared. Two-thirds of the items – includingmanual handling, fire and emergency drills, teaching resources, communicationsand workplace arrangements – reveal a statistically significant inter-group divergenceof opinion, with staff consistently more confident of the orientation’s effectiveness.More than half the students were unsure on arrival as to whether the staff wereexpecting them. Two-thirds said they had not been told, or were unsure if theyhad been told, what to do if upset or anxious.Staff satisfaction with the orientation’s quality was greater than student datawarranted. Substantial institutional, procedural and behavioural changes seem necessaryif student expectations of their clinical placements are to be met and a positive,attractive image of the sector conveyed.